Agent’s Competence and Relationship Marketing Capability: A Study of Life Insurance Agents in Indonesia Using a Structural Equation Modelling Approach - Rully Adriana Swarnaputra (International Journal Labs, 2026)
The life insurance industry in Indonesia continues to grow significantly but faces persistent challenges related to low public trust, largely due to claim disputes and insurance company bankruptcies. Insurance agents play a crucial role as the primary link between companies and customers, where their relational behaviors and professional competence shape customer perceptions and loyalty. This study examined the effects of Customer Relationship Building Behavior (CRBB) and agent competence on customer trust, customer satisfaction, and renewal intention in the Indonesian life insurance industry, with agent competence representing the knowledge, skills, and professional attitudes of insurance agents. A quantitative survey was conducted with 237 life insurance policyholders in the Jabodetabek region and analyzed using PLS-SEM. The results showed that approaching and common grounding had a positive effect on customer trust, while only communication had a positive effect on customer satisfaction. Agent competence had positive effects on both customer trust and customer satisfaction. Furthermore, customer trust enhanced customer satisfaction and renewal intention, while customer satisfaction was the strongest predictor of renewal intention. The study concluded that, in the Indonesian life insurance industry, agent competence is a key driver of customer trust, satisfaction, and loyalty. These findings provide both theoretical contributions to relationship marketing literature and practical implications for insurance companies in developing agent training programs that emphasize technical competence and transparent communication. They also offer implications for regulators in strengthening professional certification requirements to reduce information asymmetry and enhance consumer protection.